2(6-2y)=-1(4y-9)

Simple and best practice solution for 2(6-2y)=-1(4y-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(6-2y)=-1(4y-9) equation:


Simplifying
2(6 + -2y) = -1(4y + -9)
(6 * 2 + -2y * 2) = -1(4y + -9)
(12 + -4y) = -1(4y + -9)

Reorder the terms:
12 + -4y = -1(-9 + 4y)
12 + -4y = (-9 * -1 + 4y * -1)
12 + -4y = (9 + -4y)

Add '4y' to each side of the equation.
12 + -4y + 4y = 9 + -4y + 4y

Combine like terms: -4y + 4y = 0
12 + 0 = 9 + -4y + 4y
12 = 9 + -4y + 4y

Combine like terms: -4y + 4y = 0
12 = 9 + 0
12 = 9

Solving
12 = 9

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| X+8+4=2(x+4) | | 6(-3z+2)=-5z+11z-12 | | X^2+2z-15=0 | | 2z-6=2(z+2)-10 | | 1.6u+7.2=-2.4u-4.8 | | 2(-6x-1)=-3(-4x-3) | | 2(6-2y)=-1(-4y-9) | | 2x+5-x=(20-4x)+2x | | 0.6x^2+2.4x+0.6=0 | | Y^2+18=9y | | 5x+6=2+3x | | -0.6x^2+2.4x+0.6=0 | | 10x^3=640 | | (9y^2-3y+5y)+(y^2+6y^2+9y)= | | x/2+x/4=15 | | X+8=x+4 | | x+17.6=2.9 | | x+9x/5=70 | | X/2=X/9+3/2 | | -7=-7+x | | (2a-4)(a^2-8a+1)= | | 5/3+X/2=5/6 | | 3/8=50/p | | 116-5x=4x+18 | | 0=2x-5x^2 | | -27+y=2 | | y=1/6x-3 | | (x+2)^2/3=9 | | 78593478=65656+79 | | 5x-(x-30)=100 | | 66(x+11)=121(x+6) | | x=-2y-z+4 |

Equations solver categories